Anti-Cancer Effects of Trigonella foenum in Neuroblastoma Cell Line - İrem Ürkmez; Hatice İlayhan Karahan Coven; Aslı Eldem; Melek Pehlivan (European Journal of Biology)
Objective: Current approaches focus on the use of natural compounds in plants in the treatment of cancer. Trigonella foenum (Fenugreek) is mainly used in medicine, food, and cosmetics due to its bioactive and aromatic compounds. Many compounds with medicinal effects are found in Fenugreek seeds. These compounds have been demonstrated to be effective on numerous cancer cells. Neuroblastoma is one of the most common extracranial solid malignancies in children. In our study, the effects of Fenugreek on cell cytotoxicity, cell damage, migration, and sphere formation in neuroblastoma cells were investigated. Materials and Methods: The powder extract was dissolved in DMEM and filtered to prepare a stock solution of Fenugreek. We used MTT assay for the detection of cytotoxic effects of Fenugreek on SH-SY5Y cells, crystal violet staining for the analysis of morphological change in cells, wound healing test for the cell migration analysis, and agarose gel electrophoresis for detecting DNA damage. We created a spheroid to test the effect we observed in 2D culture, in 3D culture as well. Results: The findings of our study showed that Fenugreek treatments caused significant reductions in cell proliferation and migration capacities in 2D neuroblastoma cells at IC50 (1500 μg/ml) doses, respectively. In addition Fenugreek changed cell morphology and increased DNA fragmentation. Furthermore, Fenugreek caused disruption of 3D spheroid formation of SHSY-5Y cells in a dose- and time-dependent manner. Conclusion: The determination of the anti-cancer effect of Fenugreek on neuroblastoma cancer may be a useful and feasible intervention in neuroblastoma patients in the light of further studies and with the help of new nano drug delivery systems.